Concrete production using marble powder and marble coarse aggregates: an analysis of mechanical properties and sustainability - Saloua Filali; Abdelkader Nasser (Budownictwo i Architektura)
The growing demand for concrete driven by infrastructure and urbanization puts pressure on natural resources and harms the ecosystem. Using recycled materials like waste marble powder (WMP) and marble coarse aggregates (MCA) in concrete can address this demand while maintaining quality. This study explores the mechanical properties of eco-friendly concrete with varying levels of marble waste substitution, replacing cement with WMP (0%-10%) and natural aggregates with MCA (10%-90%). A combination of destructive and non-destructive tests, including the Schmidt hammer and ultrasonic velocity tests, was used to assess flexural, compressive, and split tensile strengths. Results showed a 15.78% increase in workability when marble coarse aggregates were added. Compressive strength gained up to 44.02% on day 14 with 10% marble powder and 70% marble aggregates, compared to the control mixture. Split tensile strength improved by 11.02%, 11%, and 10.33% on days 7, 14, and 28, respectively, for mixes with 70% marble aggregates. Ultrasonic pulse velocity ranged from 3.68 km/s to 4.71 km/s, indicating no negative impact on concrete quality. The Schmidt hammer results correlated well with compressive strength from destructive tests. Overall, the study highlights the potential of using marble waste as an effective substitute for natural aggregates in concrete.